Normothermic machine perfusion for the assessment and transplantation of declined human kidneys from donation after circulatory death donors. Issue 4 (6th December 2017) - Hosgood, S. A.; Thompson, E.; Moore, T.; Wilson, C. H.; Nicholson, M. L.
Abstract: Background: A significant proportion of donation after circulatory death (DCD) kidneys are declined for transplantation because of concerns over their quality. Ex vivo normothermic machine perfusion (NMP) provides a unique opportunity to assess the quality of a kidney and determine its suitability for transplantation. Methods: In phase 1 of this study, declined human DCD kidneys underwent NMP assessment for 60 min. Kidneys were graded 1–5 using a quality assessment score (QAS) based on macroscopic perfusion, renal blood flow and urine output during NMP. In phase 2 of the study, declined DCD kidneys were assessed by NMP with an intention to transplant them. Results: In phase 1, 18 of 42 DCD kidneys were declined owing to poor in situ perfusion. After NMP, 28 kidneys had a QAS of 1–3, and were considered suitable for transplantation. In phase 2, ten of 55 declined DCD kidneys underwent assessment by NMP. Eight kidneys had been declined because of poor in situ flushing in the donor and five of these were transplanted successfully. Four of the five kidneys had initial graft function. Conclusion: NMP technology can be used to increase the number of DCD kidney transplants by assessing their quality before transplantation.